A conductor's analysis: John Mackey's Wine-dark sea: symphony for band - Weber, Shannon Denise, author; Phillips, Rebecca, advisor; Grapes, K. Dawn, committee member; Kenney, Wes, committee member; Pedrós-Gascón, Antonio, committee member (Colorado State University. Libraries, 2020)
This thesis provides a study of the composer John Mackey and his music. In the last twelve years, Mackey has become internationally renowned and one of the most widely performed composers in the band world. Mackey has received numerous awards and honors for his musical contributions. His unique compositional style is distinguishable in his works regardless of the genre. Audiences, conductors, and performers alike continue to find enjoyment in his music due to his creative, rhythmic, and unique scoring for winds and percussion. This document includes biographical information on the composer, provides insight into his compositional style, and thoroughly analyzes the symphony for band, Wine-Dark Sea. Wine- Dark Sea was commissioned in 2014 by Jerry Junkin and the University of Texas Wind Ensemble, in celebration of the 100th anniversary of the Sarah and Ernest Butler School of Music. The symphony is a programmatic piece that tells the story of Odysseus, Homer's hero from The Odyssey, through three exciting and dramatic movements. Distinctive characteristics of this piece include Mackey's unique use of meter changes, extended techniques in winds and percussion, and recurring programmatic themes. Wine-Dark Sea is Mackey's longest work to date, one of his most challenging works for performers and conductor, and is especially captivating for the audience.